Topical Promethazine Side Effects: Our Experience and Review of the Literature. (19th November 2013) - Cantisani, C.; Ricci, S.; Grieco, T.; Paolino, G.; Faina, V.; Silvestri, E.; Calvieri, S.
Abstract : Promethazine hydrochloride is a first-generation H1 receptor antagonist, antihistamine, and antiemetic medication that can also have strong sedative effects. The apparent ability of topical H1r/2r antagonists to target epidermal H1/2r was translated into increased efficacy in the treatment of inflammatory dermatoses, likely due to decreased inflammation and enhanced barrier function.